INDUSTRIAL DEVICE INTEGRATION AND VIRTUALIZATION FOR SMART FACTORIES - Martins, André Fagundes (2021)
Given the constant industry growth and modernization, several technologies have been introduced in the shop floor, in particular regarding industrial devices. Each device brand and model usually requires different interfaces and communication protocols, a technological diversity which renders the automatic interconnection with production management software extremely challenging. However, combining key technologies such as machine monitoring, digital twin and virtual commissioning, along with a complete communication protocol like OPC UA, it is possible to contribute towards industrial device integration on a Smart Factory environment. To achieve this goal, several methodologies and a set of tools were defined. This set of tools, as well as facilitating the integration tasks, should also be part of a virtual engineering environment, sharing the same virtual model, the digital twin, through the complete lifecycle of the industrial device, namely the project, simulation, implementation and execution/monitoring/supervision and, eventually, decommissioning phases. A key result of this work is the development of a set of virtual engineering tools and methodologies based on OPC UA communication, with the digital twin implemented using RobotStudio, in order to accomplish the complete lifecycle support of an industrial device, from the project and simulation phases, to monitoring and supervision, suitable for integration in Industry 4.0 factories. To evaluate the operation of the developed set of tools, experiments were performed for a test scenario with different devices. Other relevant result is related with the integration of a specific industrial device – CNC machining equipment. Given the variety of monitoring systems and communication protocols, an approach where various solutions available on the market are combined on a single system is followed. These kinds of all-in-one solutions would give production managers access to the information necessary for a continuous monitoring and improvement of the entire production process.